Emotional and Behavioral Difficulties, Communication, Intelligence, and Reasoning in Children with Hearing Difficulties - Olga María Alegre de la Rosa; Luis Miguel Villar Angulo (MDPI AG, 2019)
This study aims to investigate whether emotional and behavioral difficulties (EBD) differ between children with cochlear implants (CIs) or hearing aids (HAs), according to multi-informant ratings. Methods: A battery of psychological measures (e.g., Strengths and Difficulties Questionnaire (SDQ), Illinois Test of Psycholinguistic Abilities (ITPA), Peabody Image Vocabulary Test (PPVT), and Raven Progressive Matrices Test (RPM), was administered to children with CIs or HAs. The study involved 187 children with CIs, 113 children with HAs, 176 fathers and mothers, and 300 schoolteachers. Results: Significant disagreements were found between children, parents, and schoolteachers with regard to SDQ ratings. Total SDQ difficulties score correlated poorly with other outcomes (e.g., total ITPA, final PPVT, and final RPM). Regression linear analyses showed six socio-demographic and linguistic covariates that significantly predicted children’s total SDQ difficulties score. Conclusion: Several independent variables were found to be associated with children’s total EBD scores. This article highlights the importance of providing professionals with sufficient training so that they are knowledgeable about the procedures they are to use to support children with EBD (e.g., developing and implementing instructional approaches for school students with EBD).